2021
DOI: 10.1186/s12864-021-07439-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide miRNA analysis and integrated network for flavonoid biosynthesis in Osmanthus fragrans

Abstract: Background Osmanthus fragrans is an important economical plant containing multiple secondary metabolites including flavonoids and anthocyanins. During the past years, the roles of miRNAs in regulating the biosynthesis of secondary metabolites in plants have been widely investigated. However, few studies on miRNA expression profiles and the potential roles in regulating flavonoid biosynthesis have been reported in O. fragrans. Results In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…The transcripts per million mapped reads (TPM) of these conserved miRNAs varied from 19.3 (ghy-miR5368) to 330,150 (ghy-miR166e), suggesting that the expression patterns of the various miRNAs are extremely different. Five miRNA families (ghy-miR162, ghy-miR166, ghy-miR319, ghy-miR6113 and ghy-miR6118; comprising 10 individual miRNAs) are highly expressed (TPM ≥ 10,000) at S1, S3 or S6, which is similar to previous results in Carya cathayensis [67] and Osmanthus fragrans [68]. In addition, eight conserved miRNA families, i.e., ghy-miR156, ghy-miR160, ghy-miR164, ghy-miR167, ghy-miR168, ghy-miR171, ghy-miR172 and ghy-miR390, showed moderate expression levels (TPM between 100 and 10,000) at S1, S3 or S6.…”
Section: Conserved and Novel Mirnas In Gerbera Ray Petalssupporting
confidence: 87%
“…The transcripts per million mapped reads (TPM) of these conserved miRNAs varied from 19.3 (ghy-miR5368) to 330,150 (ghy-miR166e), suggesting that the expression patterns of the various miRNAs are extremely different. Five miRNA families (ghy-miR162, ghy-miR166, ghy-miR319, ghy-miR6113 and ghy-miR6118; comprising 10 individual miRNAs) are highly expressed (TPM ≥ 10,000) at S1, S3 or S6, which is similar to previous results in Carya cathayensis [67] and Osmanthus fragrans [68]. In addition, eight conserved miRNA families, i.e., ghy-miR156, ghy-miR160, ghy-miR164, ghy-miR167, ghy-miR168, ghy-miR171, ghy-miR172 and ghy-miR390, showed moderate expression levels (TPM between 100 and 10,000) at S1, S3 or S6.…”
Section: Conserved and Novel Mirnas In Gerbera Ray Petalssupporting
confidence: 87%
“…The miRNAs we considered in this study have previously been identified in other plant species as playing a role in hybridization [ 59 ], growth regulation [ 60 , 61 , 62 , 63 ] and in response to various biotic and abiotic stresses including nutrient deficiency, drought, cold and salinity [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Moreover, miRNAs of the miR396 family are known to target oxidases, including cytochromes involved in xenobiotic detoxification [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that the differences in the samples and detection methods might be the cause of the diversity in the results. In addition, the processes of culm color deposition are complex, and many regulatory factors (TFs and miRNAs) may participate in the flavonoid synthesis pathway (Shi et al, 2021 ; Lv et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%